The Diet of Two Species of Peanut worms (Soft Substrate, Sipunculus nudus) and (Hard Substrate, Antillesoma antillarum) - Ainil Syamin, Alias (Universiti Malaysia Sarawak (UNIMAS), 2015)
Peanut worm is a type of marine soft bodied and non-segmented coelom worm. Peanut worm usually lives in temperate, subtropical, and tropical regions. In recent years, peanut worm become popular among countries such as Vietnam, Taiwan and China as special food of high nutritional and pharmaceutical value. Besides, peanut worm plays an important role as source of energy for fish, gastropods, cephalopods, carnivorous worms, crabs, starfishes and anemones. In Sarawak, peanut worm is usually use as fish bait among the local people. However, the basic knowledge especially the diet of peanut worm is still poor. Hence, this study was designed (1) to investigate the types of food with the body size of peanut worm (Sipunculus nudus and Antillesoma antillarum) and (2) to study the relationship between food items in gut content of peanut worm with the sampling locations (Kg. Pugu, Kg. Lebak and Pantai Puteri). The gut of S. nudus consist of foraminifera, foraminifera fragments, polychaete and unidentified plant materials while in the gut of A. antillarum, only sediments had been found. Besides, result showed that the highest percentage of Index Relative Importance (%IRI) was foraminifera in gut of large S. nudus but absence in small individuals. %IRI based on locations proved that foraminifera was the important food items. The gut length (cm) was positively significant correlated with the gut weight (g) in large S. nudus (r = 0.941, p = 0.002, n = 7) and gut of A. antillarum (r = 0.710, p = 0.000, n= 30). From this research, the data provided knowledge for local people and researchers in Malaysia in order to manage the resource sustainability.